Work Life Balance: Studi Fenomenologi Pada Lembaga Pendidikan - Fadilah, Muhamad Irfan; Supriatna, Dede; Suharyat, Yayat (LPPM Institut Pendidikan Nusantara Global, 2024)
In an era of globalization that continues to develop with increasingly fierce competition, the teaching and academic profession has become a key element in ensuring the sustainability of a country's educational aspects. Teachers and academics in the field of education are individuals who have a big responsibility to lead educational institutions, both formal and non-formal, in providing education to students from generation to generation. The balance between work and personal life, often referred to as work-life balance, has become an increasingly important topic in discussions about workplace well-being. This research aims to deepen the analysis of teachers and academics in their efforts to achieve balance between demanding work lives and diverse personal lives. Through a phenomenological approach, we will explore the world of teachers and academics from their own perspective, understanding their feelings, thoughts and experiences in facing these challenges. Based on the results of this research, it shows that work life balance in the teaching profession and academics who work in the educational environment can be achieved with various supporting and inhibiting factors. Primarily, the biggest supporting factor in achieving work-life balance is determined by self-management in dividing needs in the world of work and in the personal world such as home and family. This self-management certainly cannot be measured by the same standards because of the similarities between the teaching and academic professions, between one individual and another individual who has different backgrounds, positions and responsibilities. Therefore, the work life balance expected for each individual is certainly different from one individual to another.